Is surveillance imaging in pediatric patients treated for localized rhabdomyosarcoma useful? The European experience. Issue 4 (21st November 2019) - Vaarwerk, Bas; Mallebranche, Coralie; Affinita, Maria C.; van der Lee, Johanna H.; Ferrari, Andrea; Chisholm, Julia C.; Defachelles, Anne‐Sophie; De Salvo, Gian Luca; Corradini, Nadège; Minard‐Colin, Veronique; Morosi, Carlo; Brisse, Hervé J.; et al.
Abstract : Background: After the completion of therapy, patients with localized rhabdomyosarcoma (RMS) are subjected to intensive radiological tumor surveillance. However, the clinical benefit of this surveillance is unclear. This study retrospectively analyzed the value of off‐therapy surveillance by comparing the survival of patients in whom relapse was detected by routine imaging (the imaging group) and patients in whom relapse was first suspected by symptoms (the symptom group). Methods: This study included patients with relapsed RMS after the completion of therapy for localized RMS who were treated in large pediatric oncology hospitals in France, the United Kingdom, Italy, and the Netherlands and who were enrolled in the International Society of Paediatric Oncology Malignant Mesenchymal Tumor 95 (1995‐2004) study, the Italian Paediatric Soft Tissue Sarcoma Committee Rhabdomyosarcoma 96 (1996‐2004) study, or the European Paediatric Soft Tissue Sarcoma Study Group Rhabdomyosarcoma 2005 (2005‐2013) study. The survival times after relapse were compared with a log‐rank test between patients in the imaging group and patients in the symptom group. Results: In total, 199 patients with relapsed RMS were included: 78 patients (39.2%) in the imaging group and 121 patients (60.8%) in the symptom group. The median follow‐up time after relapse was 7.4 years (interquartile range, 3.9‐11.5 years) for survivors (n = 86); the 3‐year postrelapse survival rate was 50% (95% confidence interval [CI], 38%‐61%) for the imaging group and 46% (95% CI, 37%‐55%) for the symptom group ( P = .7). Conclusions: Although systematic routine imaging is the standard of care after RMS therapy, the majority of relapses were detected as a result of clinical symptoms. This study found no survival advantage for patients whose relapse was detected before the emergence of clinical symptoms. These results show that the value of off‐therapy surveillance is controversial, particularly because repeated imaging may also entail potential harm. Abstract : This study assesses the clinical value of radiological surveillance imaging in pediatric patients with rhabdomyosarcoma, which is routinely performed after the completion of therapy. In the majority of patients, relapse is detected because of symptoms, and there is no evidence that early detection by imaging results in improved survival.